Peran Agama Islam dalam Konservasi Hutan - Ariyadi Ariyadi; Siti Maimunah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2017)
This research departs from the concerns that occur at this time with the nature that has started not friendly with living things in it, it can be felt like rainfall in the dry season or vice versa, many animals are becoming extinct due to higher earth temperatures, the ozone layer that began thinning which is the heat that feels stinging the skin. Maintaining the preservation of the environment is part of the noble character that must be applied in the midst of human life. This is done by maintaining the sustainability of life in the world and preventing damage, disasters that can occur coupled with the greedy human attitude by destroying nature. These forests are the source of this natural force as water stores, oxygen producers, carbon dioxide absorber, germplasm sources, sources of food and food, wildlife habitats that if not properly managed will become extinct and the survival of life on earth will end. Meanwhile, the religion of Islam as the religion Rahmatan Lil 'Alamin ordered mankind to maintain and preserve the forest as a living environment, the human being made God on this earth as khalifah, interesting Islam Islam has its own point of view about forest conservation.